A journal club for peer mentorship: helping to navigate the transition to independent practice - MacMillan, Thomas E. (Perspect Med Educ, 2016)
The transition from residency to independent practice presents unique challenges for physicians. New attending physicians often have unmet learning needs in non-clinical domains. An attending physician is an independent medical practitioner, sometimes referred to as a staff physician or consultant. Peer mentorship has been explored as an alternative to traditional mentorship to meet the learning needs of new attendings. In this article, the authors describe how a journal club for general internal medicine fellowship graduates helped ease the transition by facilitating peer mentorship. Journal club members were asked to bring two things to each meeting: a practice-changing journal article, and a ‘transition to practice’ discussion topic such as a diagnostic dilemma, billing question, or a teaching challenge. Discussions fell into three broad categories that the authors have termed: trading war stories, measuring up, and navigating uncharted waters. It is likely that physicians have a strong need for peer mentorship in the first few years after the transition from residency, and a journal club or similar discussion group may be one way to fulfil this.